Students in a psychology class look a final examination. As part of an experiment to see how much of the course content they remembered over time, they took equivalent forms of the exam in monthly intervals thereafter. The average score, f ( t ) , for the group after t months is modeled by the function f ( t ) = 76 − 18 log ( t + 1 ) , where 0 ≤ t ≤ , 12 . a. What was the average score when the exam was first given? b. What was the average score after 2 months? 4 months? 6 months? 8 months? one year? c. Use the results from parts (a) and (b) to graph f. Describe what the shape of the graph indicates in terms of the material retained by the students.
Students in a psychology class look a final examination. As part of an experiment to see how much of the course content they remembered over time, they took equivalent forms of the exam in monthly intervals thereafter. The average score, f ( t ) , for the group after t months is modeled by the function f ( t ) = 76 − 18 log ( t + 1 ) , where 0 ≤ t ≤ , 12 . a. What was the average score when the exam was first given? b. What was the average score after 2 months? 4 months? 6 months? 8 months? one year? c. Use the results from parts (a) and (b) to graph f. Describe what the shape of the graph indicates in terms of the material retained by the students.
Solution Summary: The author explains how the average score for the group after t months is modeled as f(t)=76-18mathrmlog
Students in a psychology class look a final examination. As part of an experiment to see how much of the course content they remembered over time, they took equivalent forms of the exam in monthly intervals thereafter. The average score,
f
(
t
)
, for the group after t months is modeled by the function
f
(
t
)
=
76
−
18
log
(
t
+
1
)
, where
0
≤
t
≤
,
12
.
a. What was the average score when the exam was first given?
b. What was the average score after 2 months? 4 months? 6 months? 8 months? one year?
c. Use the results from parts (a) and (b) to graph f. Describe what the shape of the graph indicates in terms of the material retained by the students.
Solve the system of equation for y using Cramer's rule. Hint: The
determinant of the coefficient matrix is -23.
-
5x + y − z = −7
2x-y-2z = 6
3x+2z-7
eric
pez
Xte
in
z=
Therefore, we have
(x, y, z)=(3.0000,
83.6.1 Exercise
Gauss-Seidel iteration with
Start with (x, y, z) = (0, 0, 0). Use the convergent Jacobi i
Tol=10 to solve the following systems:
1.
5x-y+z = 10
2x-8y-z=11
-x+y+4z=3
iteration (x
Assi 2
Assi 3.
4.
x-5y-z=-8
4x-y- z=13
2x - y-6z=-2
4x y + z = 7
4x-8y + z = -21
-2x+ y +5z = 15
4x + y - z=13
2x - y-6z=-2
x-5y- z=-8
realme Shot on realme C30
2025.01.31 22:35
f
Use Pascal's triangle to expand the binomial
(6m+2)^2
Chapter 4 Solutions
Algebra And Trigonometry 6th. Edition Annotated Instructor's Copy Blitzer
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, algebra and related others by exploring similar questions and additional content below.
Bayes' Theorem 1: Introduction and conditional probability; Author: Dr Nic's Maths and Stats;https://www.youtube.com/watch?v=lQVkXfJ-rpU;License: Standard YouTube License, CC-BY
What is Conditional Probability | Bayes Theorem | Conditional Probability Examples & Problems; Author: ACADGILD;https://www.youtube.com/watch?v=MxOny_1y2Q4;License: Standard YouTube License, CC-BY
Bayes' Theorem of Probability With Tree Diagrams & Venn Diagrams; Author: The Organic Chemistry Tutor;https://www.youtube.com/watch?v=OByl4RJxnKA;License: Standard YouTube License, CC-BY